Combination of Experimental Design and Desirability Function as a Genuine Method to Achieve Common Optimal Conditions for the Adsorption of Pb(II) and Cu(II) onto the Poplar Tree Leaves: Equilibrium, Kinetic and Thermodynamic Studies - Salma Jadali; S. Maryam Sajjadi; Hassan Zavvar Mousavi; Maryam Rajabi (Analytical and Bioanalytical Chemistry Research, 2017)
In this study, the ashes of poplar tree leaves are applied as an efficient, accessible and inexpensive biosorbent for the removal of heavy metals Pb2+ and Cu+2 in aqueous solutions. In the adsorption processes, the success of the ions removal highly depends on the level of several experimental factors such as pH, contact time, adsorbent dosage and temperature. Therefore, a genuine statistical experiment design method is required to achieve a common experimental conditions where both ions have been removed from aqueous solutions to a great degree. Here, this common optimal conditions are obtained by the combination of experimental design and desirability function methods. For a mixture of Pb2+ and Cu+2, the following optimal conditions were achieved: pH of 5.4, contact time of 23 min, adsorbent dosage of 0.14 g, and temperature of 280C; at 150 mg L-1 of Pb2+ and 120 mg L-1 Cu2+. The removal efficiencies of Pb2+ and Cu+2 were 92.8% and 94.9%, respectively, which verified the applicability of this biosorbent for the ions removal. Moreover, the equilibrium and kinetic behavior of the adsorption processes are investigated and then thermodynamic parameters, ΔG0(Kj mol-1), ΔH(Kj mol-1)0, and ΔS0 (Kj mol-1), are evaluated which reveal that both processes are endothermic and spontaneous.